KONDISI SOSIAL EKONOMI DAN PERSEPSI MASYARAKAT PEMBUKA LAHAN DI KAWASAN CAGAR ALAM DUSUN BESAR KOTA BENGKULU. - Deselina, Daselina; Purwoko, Agus; Fajri, M. (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2004)
Dusun Besar is located in town area of Bengkulu. Dusun Besar preserve area has multi functions, i.e. as a natural habitat of Orchid Pencil (Vanda Hookeriana), and as an area of relocation of freshwater (reservoir), and water diffusion area. The aim of this research was to analyze condition of economic social and perception society about preserving of Dusun Besar behavior in farm clearing. Second investigating relation between social economic condition and perception eagar Alam Dusun Besar with its behavior in opening of farm in Dusun Besar. The research was conducted in Dusun Besar Orchard area. Amount of responder were 15 % from total population farm in Preserve Area. Data analysis use qualitative and quantitative analysis. Earnings of responder have real relation to its behavior in farm cleaning in Dusun Besar. While education level, family responsibility, and perception of respondent do not correlate to behavior in farm in Preserve Area. Socio economic determinants